2020
DOI: 10.1002/cplu.201900709
|View full text |Cite
|
Sign up to set email alerts
|

A Weakly Antiferromagnetically Coupled Biradical Combining Verdazyl with Nitronylnitroxide Units

Abstract: An antiferromagnetically (AFM) coupled biradical based on oxoverdazyl and nitronylnitroxide was synthesized in 46 % yield using Sonogashira coupling. The obtained heterobiradical evidenced distinct properties of both radical entities in solution. Depending on the solvent, the prepared biradical crystallized in two different forms. SQUID magnetization measurements on Form II showed coupling constants J intraII /k B = À 2.1 K and zJ interII / k B = À 11.5 K. Consequently, total intermolecular exchange interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…As has been reported previously, the position of the iodo‐phenyl substituent in ‘Kuhn'‐verdazyl structure dramatically affects on the reaction rate: ‘Kuhn'‐verdazyl 1a with the 4‐iodophenyl substituent at N1 demonstrates higher reactivity than 1d in Sonogashira coupling[11d] and oxidative addition . In our study, we observed a similar effect in the reactions of 1a with 2c or 2d , yielding hetero‐diradicals 4ac and 4ad , respectively (Table , Entries 6 and 7).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…As has been reported previously, the position of the iodo‐phenyl substituent in ‘Kuhn'‐verdazyl structure dramatically affects on the reaction rate: ‘Kuhn'‐verdazyl 1a with the 4‐iodophenyl substituent at N1 demonstrates higher reactivity than 1d in Sonogashira coupling[11d] and oxidative addition . In our study, we observed a similar effect in the reactions of 1a with 2c or 2d , yielding hetero‐diradicals 4ac and 4ad , respectively (Table , Entries 6 and 7).…”
Section: Resultsmentioning
confidence: 88%
“…Our study was focused on the Sonogashira coupling of iodine‐substituted radicals 1a – 1f with ethynyl‐containing building blocks 2a – 2f (Figure ). The reaction was carried out in the previously optimized conditions[11a] for stable radical alkynylation: iodide 1 (1 equiv.) and ethynyl building block 2 (1.5 equiv.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations